An Analysis of the Main Characters’ Conflicts in The Movie Memoir of a Snail - Genovthree Hawarany; Eka Fitriana; Sartika - Hijriati (Universitas Muhammadiyah Mataram, 2026)
This study aims to identify the types of conflicts experienced by the main characters in the movie Memoir of a Snail and to analyze the unfulfilled needs that cause these conflicts. This study employed a descriptive qualitative method. The subjects studied were the main characters, Grace and Gilbert; the primary data source was the movie Memoir of a Snail and its transcript. Data was collected using the documentation method by repeatedly watching the movie and highlighting relevant dialogues and scenes. The data was then analyzed using Kenney's (1966) theory to classify conflicts and Maslow's (1970) hierarchy of needs to understand their needs. The findings reveal that the main characters face both internal conflicts (loneliness, trauma, anxiety, and the desire for freedom) and external conflicts (Man vs Man and Man vs Environment). This study concludes that these conflicts occur as a direct result of the main characters' unfulfilled needs. The absence of safety, love and belonging, esteem, and self-actualization needs creates significant emotional and social tension, which triggers their internal and external conflicts. This analysis provides insight into what specific unfulfilled needs serve as the primary cause of conflicts within the movie. It is suggested that future researchers explore this movie using different theories to gain a more comprehensive understanding.